Somatostatin analogues improve health‐related quality of life in polycystic liver disease: a pooled analysis of two randomised, placebo‐controlled trials. Issue 5 (1st July 2015) - Neijenhuis, M. K.; Gevers, T. J. G.; Nevens, F.; Hogan, M. C.; Torres, V. E.; Kievit, W.; Drenth, J. P. H.
Summary Background Polycystic liver disease is associated with impaired health‐related quality of life (HRQL). Somatostatin analogues reduce hepatomegaly in polycystic liver disease. Aim To determine whether somatostatin analogues improve HRQL and to identify factors associated with change in HRQL in polycystic liver disease. Methods We pooled data from two randomized, double‐blind, placebo‐controlled trials that evaluated HRQL using the Short‐Form 36 (SF‐36) in 96 polycystic liver disease patients treated 6‐12 months with somatostatin analogues or placebo. The SF‐36 contains a summarizing physical and mental component score and was administered at baseline and at the end of treatment. We used random effect models to delineate the effect of somatostatin analogues on HRQL. We determined the effect of demographics, height‐adjusted liver volume, change in liver volume, somatostatin analogue‐associated side effects with change in HRQL. In patients with autosomal dominant polycystic kidney disease, we estimated the effect of height‐adjusted kidney volume and change in kidney volume in relation to HRQL. Results Physical component scores improved with somatostatin analogues, but remained unchanged with placebo (3.41 ± 1.29 vs. −0.71 ± 1.54, P = 0.044). Treatment had no impact on the mental component score. Large liver volume was independently associated with larger HRQL decline during follow up (−4.04 ± 2.02 points per logarithm liver volume, P = 0.049). In autosomal dominant polycystic kidney disease, patients with large liver and kidney volumes had larger decline in HRQL (5.36 ± 2.54 points per logarithm liver volume; P = 0.040 and −4.00 ± 1.88 per logarithm kidney volume; P = 0.039). Conclusion Somatostatin analogues improve HRQL in symptomatic polycystic liver disease. Halting the progressive nature of polycystic liver disease is necessary to prevent further decline of HRQL in severe hepatomegaly.